2020
DOI: 10.1038/s41419-020-2729-0
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic non-protein-coding RNA 01446 facilitates the proliferation and metastasis of gastric cancer cells through interacting with the histone lysine-specific demethylase LSD1

Abstract: Growing evidences illustrated that long non-coding RNAs (lncRNAs) exhibited widespread effects on the progression of human cancers via various mechanisms. Long intergenic non-protein-coding RNA 01446 (LINC01446), a 3484-bp ncRNA, is known to locate at chromosome 7p12.1. However, its biological functions and specific action mechanism in gastric cancer (GC) are still unclear. In our study, LINC01446 was proved to be markedly upregulated in GC tissues relative to the normal tissues, and positively correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Xu et al have validated that PVT1 with upregulated expression in GC through activation of FOXM1 transcription acts as a oncogene. (Lian et al, 2020). Additionally, a study confirmed AK023391 as a novel oncogenic lncRNA in GC that exhibited functions by mediating the PI3K-Akt signaling pathway (Huang et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Xu et al have validated that PVT1 with upregulated expression in GC through activation of FOXM1 transcription acts as a oncogene. (Lian et al, 2020). Additionally, a study confirmed AK023391 as a novel oncogenic lncRNA in GC that exhibited functions by mediating the PI3K-Akt signaling pathway (Huang et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…LINC01446 functions as an oncogene and promotes GC and glioblastoma progression and indicates a poor prognosis, an effect similar to that predicted here. (Lian et al, 2020;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins of the Jumonji C (JmjC) containing family are mainly composed of 2-oxoglutarate (2OG)- and Fe 2+ -dependent histone demethylase, of which JMJD6 is an important member [ 101 ]. In recent years, JMJD6 has been thought to be related to the occurrence and development of a variety of tumors, including breast cancer, melanoma, oral cancer, glioblastoma, hepatocellular carcinoma, colon cancer, ovarian cancer and neuroglioma [ 101 110 ]. For instance, in ovarian cancer, Zheng et al found that JMJD6 was highly expressed in tumor cells by tissue microarray immunohistochemical staining, and the high expression was associated with poor prognosis of patients [ 108 ].…”
Section: Epigenetic Regulation Of Hifs Activitymentioning
confidence: 99%
“… 7 , 8 Aberrant expression of lncRNAs may lead to dysregulation of proliferation, survival, and metastasis of tumor cells. 9 For example, lncRNA JPX is upregulated in lung cancer and promotes tumor development through targeting miR-145/CCND2 axis. 10 LncRNA OIP5-AS1 overexpression contributes to proliferation, migration, and invasion in pancreatic ductal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%